Macroline–Sarpagine Bisindole Alkaloids with Antiproliferative Activity from Alstonia penangiana - Yeap, Joanne Soon Yee; Saad, Hazwani Mat; Tan, Chun Hoe; Sim, Kae Shin; Lim, Siew Huah; Low, Yun Yee; Kam, Toh Seok (American Chemical Society, 2019)
A methanol extract of the stem bark of the Malayan Alstonia penangiana provided seven new bisindole alkaloids, comprising six macroline-sarpagine alkaloids (angustilongines E-K, 1-6) and one macroline-pleiocarpamine bisindole alkaloid (angustilongine L, 7). Analysis of the spectroscopic data (NMR and MS) of these compounds led to the proposed structures of these alkaloids. The macroline-sarpagine alkaloids (1-6) showed in vitro growth inhibitory activity against a panel of human cancer cell lines, inclusive of KB, vincristine-resistant KB, PC-3, LNCaP, MCF7, MDA-MB-231, HT-29, HCT 116, and A549 cells (IC50 values: 0.02-9.0 μM). Copyright © 2019 American Chemical Society and American Society of Pharmacognosy.